ANALYSIS OF THE CONTENT OF CONTRACTS FOR THE PROVISION OF COMMUNICATION SERVICES - Xursanov Rustam (Scholars Digest Publishing, 2023)
This article discusses the formation of civil law regulation of digital rights, theoretical and legal analysis of digital law, the concept and essence of digital rights, the need to define digital rights, the relationship of digital law with other rights, civil law analysis of digital law, theoretical and practical problems of the introduction of digital rights as a special object in civil circulation, conducted comparative analysis of the conceptual foundations for determining the rights and obligations of subjects of digital law, as well as scientific meta-methodological foundations of the categorization of digital rights in civil law.
Keywords: Keywords: sustainable energy transition, metropolises, renewable energy, urban planning, Tashkent